Light and complex 3D MoS2/graphene heterostructures as efficient catalysts for the hydrogen evolution reaction. Issue 4 (17th January 2020) - Teich, Jonah; Dvir, Ravit; Henning, Alex; Hamo, Eliran R.; Moody, Michael J.; Jurca, Titel; Cohen, Hagai; Marks, Tobin J.; Rosen, Brian A.; Lauhon, Lincoln J.; Ismach, Ariel
Abstract : Atomic Layer Deposition of MoS2 with controlled crystallinity on nanoporous graphene foams are highly promising hierarchical materials for numerous applications. A trade-off between the defect density and crystallinity for improved HER performance is reported. Abstract : Multi-component 3D porous structures are highly promising hierarchical materials for numerous applications. Herein we show that atomic-layer deposition (ALD) of MoS2 on graphene foams with variable pore size is a promising methodology to prepare complex 3D heterostructures to be used as electrocatalysts for the hydrogen evolution reaction (HER). The effect of MoS2 crystallinity is studied and a trade-off between the high density of defects naturally presented in amorphous MoS2 coatings and the highly crystalline phase obtained after annealing at 800 °C is established. Specifically, an optimal annealing at 500 °C is shown to yield improved catalytic performance with an overpotential of 180 mV, a low Tafel slope of 47 mV dec −1, and a high exchange current of 17 μA cm −2 . The ALD deposition is highly conformal, and thus advantageous when coating 3D porous structures with small pore sizes, as required for real-world applications. This approach is enabled by conformal thin film deposition on porous structures with controlled crystallinity by tuning the annealing temperature. The results presented here therefore serve as an effective and general platform for the design of chemically and structurally tunable, binder-free, complex, lightweight, and highly efficient 3D porous heterostructures to be used for catalysis, energy storage, composite materials, sensors, water treatment, and more.